THE ROLE OF FUNCTIONAL ABILITY, MULTIMORBIDITY, AND DEPRESSION TO QUALITY OF LIFE OF INDONESIAN OLDER ADULTS - Yvonne Suzy Handajani; Thania Vinsalia; Elisabeth Schröder-Butterfill; Yuda Turana (The Indonesian Journal of Public Health, 2025)
Introduction: Multimorbidity significantly affects older adults' quality of life (QoL). Its prevalence among adults aged ≥60 years ranges from 24% to 83%, increases with age and is closely linked to progressive physical and functional decline. A|ims: To investigate the determinants of QoL among community-dwelling older adults in urban Jakarta, Indonesia. Methods: A cross-sectional study was conducted in several community-based home care centers in West Jakarta, Indonesia, in 2023. From a database of 2,000 older adults, 600 individuals were selected using simple random sampling for screening. After applying inclusion and exclusion criteria, 501 older adults aged ≥60 years were included in the analysis. Sociodemographic and health-related data were collected using structured interviews and direct measurements. Mult|ivar|iate log|ist|ic regress|ion analysis was performed to identify factors associated with QoL. Results: A total of 501 older adults were analyzed; most were female (67.1%) and had multimorbidity (85.6%). The mean WHOQOL-BREF scores exceeded 60, with the highest score in the psychological domain (66.8). Physical health was significantly associated with multimorbidity (OR=2.08; p=0.013), exercise (OR=1.51; p=0.029), IADL (OR=3.54; p=0.007), ADL (OR=1.69; p=0.021), and balance (OR=1.92; p=0.044). Exercise increased the likelihood of better QoL (OR=1.47; p=0.037), while depression predicted poorer quality of life (OR=1.75; p=0.020). Conclusion: Multimorbidity, functional disability, balance impairment, depression, age, and exercise were significantly associated with QoL. Improving chronic disease management, maintaining independence, promoting regular exercise, and supporting mental health can enhance older adults’ well-being. Community-based programs encouraging active lifestyles and balance training may further improve QoL in this population.